How are the Results of Allogeneic Stem Cell Transplantation in Elderly Patients? A Single-center Experience - Uysal, Ayse; Erkurt, Mehmet Alı; Kuku, Irfan; Kaya, Emin; Berber, Ilhami; Sarıcı, Ahmet; Hidayet, Emine (My University, 2023)
INTRODUCTION: In this study, we aimed to present allogeneic hematopoietic stem cell transplantation (allo-HCT) experience in elderly patients with hematological malignancy. METHODS: Thirty-five patients aged 60 years and older who underwent allo-HSCT between 2017 and 2021 were retrospectively analyzed. Patient's demographic/clinical features, and the outcomes of transplantation were reviewed. RESULTS: The median age was 63 (range, 60-74) years and 25 (77,1%) were male. Twenty-seven (60%) were diagnosed with AML, followed by MDS (n: 7, 20%). Twenty-three (65,8%) patients had intermediate, and 6 (17,1%) patients had a high hematopoietic cell transplantation-specific comorbidity index score. Karnofsky performance status of ? 90% was detected in 15 (42,9%) patients. Busulfan plus fludarabine plus anti-thymocyte globulin was used mainly as a reduced-intensity conditioning regimen, which was used in 18 (51,4%) patients. The median duration of neutrophil and platelet engraftments were 18 (range, 11-27) and 18 (range, 11-33) days, respectively. The median follow-up time was 4 months (range, 0-51), with the OS rate %14,2. The transplant-related mortality rate within the first 30 days after allo-HSCT was detected in 10 patients (28,6%) due to infection and/or GvHD. Response assessment could be performed in 25 (71,4%) patients after transplantation. The duration of PFS was 6 (range, 1-51) months in patients with response evaluation. The rate of PFS was 72% in 1 years and 5 (14,2%) patients were still alive with complete response at the last visit. DISCUSSION AND CONCLUSION: Reduced-intensity conditioning regimen has provided the important advantage in allo-HSCT, for elderly patients with hematological malignancies such as AML and MDS.
Keywords: Elderly patients; allogeneic hematopoietic stem cell transplantation; reduced-intensity conditioning regimen